The Opposition In The Shar'i Text And The Constitution - Busman Edyar; Ilda Hayati; Gusti Pangestu (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This paper aims to examine the opposition in the Islamic perspective (especially the study of verse/hadith texts) and in the Indonesian constitution. The type of research used is a literature study with a qualitative approach which is analyzed by means of content analysis. The results of the research are that the opposition in meaning as a counterweight, warning or as checks and balances, is justified in Islamic law. Even when this role is lost in the life of the state, the community will not only suffer losses but will also have the potential to receive punishment from Allah SWT. Meanwhile, from a constitutional perspective, the opposition is not literally written down, but the role of the House of Representatives with the function of controlling and supervising the administration of the state is at least a signal that opposition is not taboo in the Indonesian state system. Even the opposition is needed so that the state process can run well